PERANCANGAN MODEL OPTIMASI WAKTU PANEN AYAM BROILER DENGAN MEMPERTIMBANGKAN TOTAL ONGKOS PENGEMBANGBIAKAN AYAM - Vania Apsari, Antyesti
This study presents the development of a mathematical model used to optimize broiler harvest time by considering the estimated profit obtained. The model development is carried out by utilizing FCR (Feed Conversion Ratio) data which describes the conversion rate of animal feed. By paying attention to this pattern, calculations can be made to predict the weight growth of chickens during the breeding period. Calculations are also carried out to estimate the amount of profit obtained by considering the cost of food. Adjustments are made by making several modifications to the reference model, namely by adding the FCR bonus component to the objective function and eliminating the DOC (Day Old Chick) purchase cost component. Modifications were also made to the decision variables, constraints, parameters, and indices used in the overall model. The proposed model shows the estimated profit over the next few days, which might give the poultry owner additional insight to bargain with the buyer’s proposal regarding the profitable harvest time. Thus, it is expected that the harvest time of chickens can be adjusted to the time that will provide the greatest profit for the owner. The best alternative solution obtained from this study is chicken harvest time which is predicted to provide the greatest profit if there is a demand for 5000 chickens to harvest when the chickens are 14 days old. The solution for this condition is to delay the harvest time for one day and harvest when the chickens are 15 days old, so that the maximum profit prediction is Rp. 34,740,043.66 or 13% of the initial profit.